2010
DOI: 10.1105/tpc.110.075697
|View full text |Cite
|
Sign up to set email alerts
|

A Pseudomonas syringae ADP-Ribosyltransferase Inhibits Arabidopsis Mitogen-Activated Protein Kinase Kinases

Abstract: The successful recognition of pathogen-associated molecular patterns (PAMPs) as a danger signal is crucial for plants to fend off numerous potential pathogenic microbes. The signal is relayed through mitogen-activated protein kinase (MPK) cascades to activate defenses. Here, we show that the Pseudomonas syringae type III effector HopF2 can interact with Arabidopsis thaliana MAP KINASE KINASE5 (MKK5) and likely other MKKs to inhibit MPKs and PAMP-triggered immunity. Inhibition of PAMP-induced MPK phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
206
0
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(220 citation statements)
references
References 43 publications
3
206
0
11
Order By: Relevance
“…Studies on bacterial effectors revealed that HopAI1 inactivates MAPKs by removing the phosphate group from phosphothreonine through a unique phosphothreonine lyase activity to suppress PAMP responses , whereas HopF2 suppresses PAMP-mediated immunity by inhibiting MAPKKs (Wang et al, 2010), suggesting that targeting MAPK cascades downstream of plant immune receptors plays important roles in bacterial virulence. Since MEKK2 functions upstream of the NB-LRR R protein SUMM2, it is likely that MEKK2 evolved to sense the attack of the MEKK1-MKK1/MKK2-MPK4 kinase cascade by microbial pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on bacterial effectors revealed that HopAI1 inactivates MAPKs by removing the phosphate group from phosphothreonine through a unique phosphothreonine lyase activity to suppress PAMP responses , whereas HopF2 suppresses PAMP-mediated immunity by inhibiting MAPKKs (Wang et al, 2010), suggesting that targeting MAPK cascades downstream of plant immune receptors plays important roles in bacterial virulence. Since MEKK2 functions upstream of the NB-LRR R protein SUMM2, it is likely that MEKK2 evolved to sense the attack of the MEKK1-MKK1/MKK2-MPK4 kinase cascade by microbial pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the effectors HopAI1 and HopF2 inhibit downstream steps of the same PTI signaling pathways targeted by AvrPto and AvrPtoB. HopAI1 and HopF2 target MPKs and MKKs, respectively, which are kinases that mediate PTI signaling following perception of microbial patterns (Wang et al 2010;Wu et al 2011). This example also illustrates how the same effector could target two or more different steps within an ETP (Fig.…”
Section: Effector-targeted Pathways: Functional Redundancy Among Pathmentioning
confidence: 99%
“…Among the latter, the P. syringae effectors AvrPto, AvrPtoB, and HopF2 target PAMP receptor complex components to block PTI signaling (Göhre et al, 2008;Shan et al, 2008;Xiang et al, 2008;Gimenez-Ibanez et al, 2009;Zhou et al, 2014). In addition, HopF2 ADP ribosylates MKK5 (and possibly other MKKs), thereby blocking phosphorylation activity and interfering with immune signaling (Wang et al, 2010). At the MAPK level, MPK3, MPK4, and MPK6 are inactivated by P. syringae HopAI1, a phospho-Thr lyase, removing the phosphate group within the activation loop motif (Zhang et al, , 2012.…”
mentioning
confidence: 99%